THE EFFECT OF ZIZIPHUS MAURITIANA FRUIT EXTRACT (AS COATING) ON THE QUALITY OF CHICKEN EGGS DURING STORAGE - I K. P., Yoga; Okarini, I. A.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika; Vol 9 No 1 (2021): Vol. 9 No. 1 Tahun 2021; January - april, 2021)
This study aims to determine the quality of eggs from coating using Ziziphus mauritiana fruit extracts stored for 28 days. The research was conducted at the Laboratory of Animal Products Technology, Faculty of Animal Husbandry, Udayana University. Completely Randomized Design (CRD), consisting of 4 treatments, 3 treatments coating of Z.mauritiana fruit  extract: DC (1: 1) = with coating (1 part extract: 1 part distilled water); DC (1: 2) = with coating (1 part extract: 2 parts distilled water); DC (1: 3) = with coating (1 part extract: 3 parts distilled water) and 1 treatment without coating (TC), each treatment contains 36 eggs, 144 eggs are needed for the four treatments. Every week, analysis of egg quality was carried out (each treatment and each week of observation, nine eggs were available). The results of the statistical analysis of this study showed that during 28 days of storage, the eggs of the Z. mauritiana fruit extract treatment affected changes in egg weight, yolk index, albumen index and had not affected yolk colour, HU, and egg pH, compared to the uncoated treatment. Based on the results of statistical analysis, it was concluded that the quality of eggs stored for 28 days in DC 1: 3 treatment (1 part of Z. mauritiana fruit extract with 3 parts of distilled water) had the best egg quality in terms of albumen index, yolk index and yolk colour, compared with the other three treatments. Keywords: bidara fruit, quality of long-stored eggs, shelf life of eggs, coating of bidara fruit